Head-up display glass and head-up display system
Patent Information
- Application Number
- CN202311457600.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-03
AI Technical Summary
[0004]随着技术的进步,可以选用主要发射P偏振光的HUD投影装置,结合布儒斯特定律,玻璃对以布儒斯特角入射的P偏振光基本不发生反射,因此在前挡风玻璃上设置一个P偏振光增强反射涂层即可实现HUD显示的主图像,同时不会产生副图像;例如中国专利CN116568501A公开了一种用于具有P偏振辐射的平视显示系统的复合玻璃板,在第二玻璃板(即内玻璃板)的背对中间层的第二表面(即车内表面)上设置第二涂层,P偏振辐射用于生成HUD图像,第二涂层包括折射率大于或等于的介电材料第一层和折射率小于或等于1.6的介电材料第二层,第二层裸露在车内且包含基于氧化硅(SiO2)的介电材料,SiO2膜层的表面硬度较低,导致第二涂层容易被细砂砾或其他硬质部件划伤,进而影响前挡风玻璃的整体外观,甚至降低HUD图像质量
[0028]本申请所提供的抬头显示玻璃中,采用SiZrOx层或SiZrMOy层作为透明纳米膜的最外保护层,与传统的SiO2层作为透明纳米膜的最外一层相比,在保持较低折射率的同时,提高了膜层硬度和消光系数,既能够使透明纳米膜对P偏振光保持较高的反射率以保证HUD图像的高亮度和高对比度,又更有利于透明纳米膜在车内表面上的裸露使用,还出乎意料地使透明纳米膜对P偏振光的反射光谱更加平滑,有利于实现HUD图像的中性色显示。
Smart Images

Figure CN117289468B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of automotive glass, specifically providing a head-up display glass and a head-up display system. Background Technology
[0002] A head-up display (HUD) is a driver-centric, blind-operated, multi-functional instrument panel. Its function is to project important driving information such as speed and navigation onto the windshield in front of the driver, allowing the driver to see this information without looking down or turning their head, thus improving driving safety.
[0003] Traditional HUD projection devices emit projection light, primarily S-polarized light, onto the windshield. This S-polarized light is reflected from both the interior and exterior surfaces of the windshield, creating a primary image for the HUD display and a secondary image that appears as ghosting. To mitigate or eliminate the secondary image, a wedge-shaped PVB layer can be used as the intermediate adhesive layer of the windshield, allowing the secondary image to overlap with the primary image.
[0004] With technological advancements, HUD projection devices that primarily emit P-polarized light can be selected. Based on Brewster's law, glass essentially does not reflect P-polarized light incident at Brewster's angle. Therefore, a P-polarized light-enhancing reflective coating on the windshield can achieve the main image displayed in the HUD without generating a secondary image. For example, Chinese patent CN116568501A discloses a composite glass plate for a head-up display system with P-polarized radiation. A second coating is applied to the second surface (i.e., the interior surface of the vehicle) of the second glass plate (i.e., the inner glass plate) opposite to the intermediate layer. P-polarized radiation is used to generate the HUD image. The second coating includes a first layer of dielectric material with a refractive index greater than or equal to 1.6 and a second layer of dielectric material with a refractive index less than or equal to 1.6. The second layer is exposed inside the vehicle and contains a silicon oxide (SiO2)-based dielectric material. The low surface hardness of the SiO2 film makes the second coating easily scratched by fine sand or other hard parts, thus affecting the overall appearance of the windshield and even reducing the quality of the HUD image. Summary of the Invention
[0005] In order to solve the above-mentioned technical problems, the purpose of this application is to provide a head-up display glass and a head-up display system. The head-up display glass can improve the surface hardness of the P-polarized light-enhancing reflective coating without reducing the quality of the HUD image, so that the P-polarized light-enhancing reflective coating can better adapt to the exposed use environment inside the vehicle.
[0006] To achieve the above objectives, this application provides a head-up display glass, characterized in that the head-up display glass comprises:
[0007] Laminated glass, comprising an outer glass sheet, an inner glass sheet, and a thermoplastic interlayer disposed between the outer and inner glass sheets, wherein the outer glass sheet includes a first and a second surface facing away from each other, the inner glass sheet includes a third and a fourth surface facing away from each other, and the thermoplastic interlayer is disposed between the second and third surfaces; and
[0008] A transparent nanofilm is disposed on the fourth surface. The transparent nanofilm is capable of reflecting P-polarized light. The transparent nanofilm includes an outermost protective layer that is furthest from the fourth surface. The outermost protective layer is a SiZrOx layer or a SiZrMOy layer, wherein x satisfies 1 < x < 3, y satisfies 1 < y < 3, and M is selected from one or more combinations of W, Nb, Ta, Y, Hf, and Al.
[0009] The refractive index n of the outermost protective layer is 1.50-1.60, and the extinction coefficient k of the outermost protective layer is 0.00001-0.001.
[0010] In some embodiments, the pencil hardness of the outermost protective layer is ≥9H.
[0011] In some embodiments, the physical thickness of the outermost protective layer is 30nm-120nm.
[0012] In some embodiments, the outermost protective layer is formed by magnetron sputtering, and the sputtering target of the outermost protective layer is a SiZr alloy target or a SiZrM alloy target.
[0013] In some embodiments, the SiZr alloy target comprises 50%-70% Si and 30%-50% Zr by mass percentage, and the SiZrM alloy target comprises 50%-75% Si, 10%-40% Zr and 0.1%-15% M.
[0014] In some embodiments, M is selected from two or more combinations of W, Nb, Ta, Y, Hf, and Al, and the mass ratio between the most abundant element and the least abundant element in the combination is 1-2.
[0015] In some embodiments, the target power supply for the outermost protective layer is a high-power pulsed magnetron sputtering power supply, and the operating voltage for magnetron sputtering the outermost protective layer is 550V-1200V, the operating current is 200A-1000A, and the duty cycle is 5%-15%.
[0016] In some embodiments, the transparent nanofilm further includes at least one stacked structure disposed between the fourth surface and the outermost protective layer. Each stacked structure includes a high refractive index layer and a low refractive index layer stacked sequentially. The refractive index of the high refractive index layer is 1.61-2.75, and the refractive index of the low refractive index layer is 1.35-1.60.
[0017] In some embodiments, the high refractive index layer and the low refractive index layer are formed by magnetron sputtering, the target power supply for the low refractive index layer is a medium-frequency magnetron sputtering power supply, and the duty cycle for magnetron sputtering the low refractive index layer is 100%.
[0018] In some embodiments, the target power supply for the high refractive index layer is a medium-frequency magnetron sputtering power supply, and the duty cycle for magnetron sputtering the high refractive index layer is 100%.
[0019] In some embodiments, the target power supply for at least one of the high refractive index layers is a high-power pulsed magnetron sputtering power supply, and the duty cycle for magnetron sputtering at least one of the high refractive index layers is 5%-15%.
[0020] In some embodiments, the outermost protective layer is in direct contact with the low-refractive-index layer in the nearest stacked structure, and the physical thickness of the outermost protective layer is 30 nm-110 nm.
[0021] In some embodiments, the physical thickness of the low-refractive-index layer in the closest stacked structure is greater than the physical thickness of the outermost protective layer.
[0022] In some embodiments, an optical adjustment layer is further disposed between the outermost protective layer and the low refractive index layer in the nearest stacked structure, the refractive index of the optical adjustment layer being 2.10-2.75, and the physical thickness of the outermost protective layer being 60nm-120nm.
[0023] In some embodiments, the physical thickness of the outermost protective layer is greater than the thickness of the optical adjustment layer.
[0024] In some embodiments, the optical adjustment layer is formed by magnetron sputtering, and the target power supply of the optical adjustment layer is a high-power pulsed magnetron sputtering power supply, with a duty cycle of 5%-15% for magnetron sputtering of the optical adjustment layer.
[0025] In some embodiments, at least one high refractive index layer includes at least two high refractive index sublayers, wherein the high refractive index sublayer closest to the fourth surface has a refractive index of 1.61-2.10 and the high refractive index sublayer furthest from the fourth surface has a refractive index of 2.11-2.75.
[0026] In some embodiments, the reflectivity of the head-up display glass to P-polarized light with wavelengths of 629 nm, 529 nm, and 469 nm incident at an incident angle of 65° is R1, R2, and R3, respectively, wherein R1 ≥ 19%, R2 ≥ 19%, and R3 ≥ 19%.
[0027] This application also provides a head-up display system, which includes a projection device and a head-up display glass as described above. The projection device is used to generate projection light containing P-polarized light, wherein the proportion of P-polarized light in the projection light is greater than or equal to 80%, and the projection light is incident on the transparent nanofilm at an incident angle of 38° to 85°.
[0028] In the head-up display glass provided in this application, a SiZrOx layer or a SiZrMOy layer is used as the outermost protective layer of the transparent nanofilm. Compared with the traditional SiO2 layer as the outermost layer of the transparent nanofilm, it maintains a lower refractive index while improving the film hardness and extinction coefficient. This not only enables the transparent nanofilm to maintain a high reflectivity for P-polarized light to ensure high brightness and high contrast of the HUD image, but also makes it more suitable for the exposed use of the transparent nanofilm on the surface of the vehicle interior. Unexpectedly, it also makes the reflection spectrum of the transparent nanofilm for P-polarized light smoother, which is conducive to achieving neutral color display of the HUD image. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the head-up display system provided in this application.
[0030] Figure 2 This is a cross-sectional enlarged schematic diagram of the first embodiment of the transparent nanofilm provided in this application.
[0031] Figure 3 This is a cross-sectional enlarged schematic diagram of the second embodiment of the transparent nanofilm provided in this application.
[0032] Figure 4 This is a cross-sectional enlarged schematic diagram of the third embodiment of the transparent nanofilm provided in this application.
[0033] Figure 5 This is a cross-sectional enlarged schematic diagram of the fourth embodiment of the transparent nanofilm provided in this application.
[0034] Figure 6 This is a cross-sectional enlarged schematic diagram of the fifth embodiment of the transparent nanofilm provided in this application.
[0035] Figure 7 This is a cross-sectional enlarged schematic diagram of the sixth embodiment of the transparent nanofilm provided in this application. Detailed Implementation
[0036] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of this application, the technical solution of this application is described in detail below, but this should not be construed as limiting the scope of implementation of this application.
[0037] Unless otherwise stated or in case of conflict, the terms or phrases used in this application shall have the following meanings:
[0038] In this application, terms such as "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of that feature.
[0039] The values of x, y, and t in the chemical formula: If they are clearly defined, the defined range shall prevail. If they are not clearly defined, they can be determined according to the stoichiometric, substoichiometric, or superstoichiometric deposition methods used in the magnetron sputtering process.
[0040] High-temperature heat treatment: High-temperature heat treatment at least 500°C, such as the self-weight bending process or pressing bending process at 550°C to 720°C used in the production of automotive glass.
[0041] Refractive index: The refractive index is the refractive index at a wavelength of 550 nm.
[0042] like Figure 1 As shown, this application provides a head-up display system, including a projection device 100 and a head-up display glass 200. The projection device 100 is used to generate projection light 101 containing P-polarized light, wherein the proportion of P-polarized light in the projection light 101 is greater than or equal to 80%. The projection device 100 is installed inside a vehicle, and the head-up display glass 200 is typically installed on the vehicle at a mounting angle of 18° to 45°. The mounting angle is the angle between the head-up display glass 200 and the horizontal plane when the head-up display glass 200 is in the vehicle mounting state, indicating the degree of tilt of the head-up display glass 200.
[0043] To achieve the head-up display (HUD) function, a transparent nanofilm 14 capable of reflecting P-polarized light is disposed on the HUD glass 200. The projection light 101 generated by the projection device 100 is incident on the transparent nanofilm 14 at an incident angle of 38° to 85°. The transparent nanofilm 14 can reflect part of the projection light 101 to form a HUD image that can be recognized by the driver's eyes. Compared with conventional HUD glass that can only be used with S-polarized light projection light, the HUD glass and HUD system provided in this application can meet the usage needs of drivers wearing sunglasses. The HUD glass 200 has an exterior surface and an interior surface. When the HUD glass 200 is installed on a vehicle, the exterior surface is the side exposed to the outside of the vehicle, and the interior surface is the side exposed to the inside of the vehicle. The transparent nanofilm 14 is disposed on the interior surface.
[0044] The projection device 100 is used to output relevant text and image information, such as speed, engine speed, fuel consumption, tire pressure, dynamic navigation, night vision, and real-view maps, onto the head-up display glass 200, so that it can be observed by an observer inside the vehicle, realizing a head-up display (HUD), or even an augmented reality head-up display (AR-HUD). The projection device 100 is a component known to those skilled in the art, including but not limited to lasers, light-emitting diodes (LEDs), liquid crystal displays (LCDs), digital light processing (DLP), electroluminescent (EL) tubes, cathode ray tubes (CRTs), vacuum fluorescent tubes (VFDs), collimating lenses, spherical correction lenses, convex lenses, concave lenses, reflecting mirrors, and / or polarizing mirrors. Furthermore, the position and incident angle of the projection device 100 are adjustable to suit observers at different positions or heights inside the vehicle.
[0045] exist Figure 1 In this application, the head-up display glass 200 includes laminated glass and a transparent nanofilm 14. The laminated glass includes an outer glass plate 11, an inner glass plate 13, and a thermoplastic interlayer 12 disposed between the outer and inner glass plates. The outer glass plate 11 includes a first surface 111 and a second surface 112 facing away from each other. The inner glass plate 13 includes a third surface 131 and a fourth surface 132 facing away from each other. The thermoplastic interlayer 12 is disposed between the second surface 112 and the third surface 131. In this application, the transparent nanofilm 14 serves as a P-polarized light-enhancing reflective coating. The transparent nanofilm 14 is disposed on the fourth surface 132. The transparent nanofilm 14 can reflect P-polarized light, thereby improving the reflectivity of the laminated glass for P-polarized light, and thus achieving a ghosting-free head-up display function.
[0046] like Figures 2 to 7As shown, the transparent nanofilm 14 provided in this application includes an outermost protective layer 141 that is furthest from the fourth surface 132. The outermost protective layer is a SiZrOx layer or a SiZrMOy layer, wherein x satisfies 1 < x < 3, y satisfies 1 < y < 3, and M is selected from one or more combinations of W, Nb, Ta, Y, Hf, and Al. The refractive index n of the outermost protective layer 141 is 1.50-1.60, and the extinction coefficient k of the outermost protective layer is 0.00001-0.001. This application uses a SiZrOx layer or a SiZrMOy layer as the outermost protective layer 141 of the transparent nanofilm 14. Compared with the traditional SiO2 layer as the outermost layer of the transparent nanofilm 14, it maintains a lower refractive index while improving the film hardness and extinction coefficient k. This not only enables the transparent nanofilm 14 to maintain a high reflectivity for P-polarized light to ensure high brightness and high contrast of the HUD image, but also makes it more suitable for the exposed use of the transparent nanofilm 14 on the surface of the vehicle interior. Unexpectedly, it also makes the reflection spectrum of the transparent nanofilm 14 for P-polarized light smoother, which is conducive to achieving neutral color display of the HUD image. Furthermore, it reduces the visible light reflectivity of the head-up display glass 200 to the natural light inside the vehicle, which helps to improve the dashboard reflection problem when the head-up display glass 200 is used as a windshield.
[0047] In some embodiments, the outermost protective layer 141 has a pencil hardness ≥9H to facilitate the exposed use of the transparent nanofilm 14 on the interior surface of the vehicle.
[0048] In some embodiments, the physical thickness of the outermost protective layer 141 is 30nm-120nm, specifically 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, and 120nm. It is understood that if the physical thickness of the outermost protective layer 141 is less than 30nm, it is detrimental to improving the hardness, wear resistance, and scratch resistance of the transparent nanofilm 14; if the physical thickness of the outermost protective layer 141 is greater than 120nm, it is detrimental to controlling the production cost of the transparent nanofilm 14 and the neutral color display of the HUD image.
[0049] The transparent nanofilm 14 can be deposited layer by layer onto the fourth surface 132 by magnetron sputtering. By optimizing the material and thickness of each layer of the transparent nanofilm 14, the transparent nanofilm 14 can withstand subsequent high-temperature heat treatment at at least 500°C and other bending and forming processes. The optical and mechanical properties of the obtained head-up display glass 200 can meet the standards for use in vehicle glass.
[0050] Specifically, the outermost protective layer 141 is formed by magnetron sputtering. The sputtering target of the outermost protective layer 141 is a SiZr alloy target or a SiZrM alloy target. A SiZrOx layer can be sputtered and deposited using a SiZr alloy target in a process gas of Ar and O2, and a SiZrMOy layer can be sputtered and deposited using a SiZrM alloy target in a process gas of Ar and O2. Here, x satisfies 1 < x < 3, y satisfies 1 < y < 3, and M is selected from one or more combinations of W (tungsten), Nb (niobium), Ta (tantalum), Y (yttrium), Hf (hafnium), and Al (aluminum).
[0051] The SiZr alloy target comprises 50%-70% Si (silicon) and 30%-50% Zr (zirconium) by weight percentage, specifically, 55% Si and 45% Zr, or 58% Si and 42% Zr, or 60% Si and 40% Zr, or 62% Si and 38% Zr, or 64% Si and 36% Zr by weight percentage. The SiZrM alloy target comprises 50%-75% Si, 10%-40% Zr, and 0.1%-15% M by weight percentage. Specific examples include a target containing 50% Si, 40% Zr, and 10% M; or 54% Si, 38% Zr, and 8% M; or 56% Si, 30% Zr, and 14% M; or 58% Si, 37% Zr, and 5% M; or 60% Si, 28% Zr, and 12% M; or 65% Si, 30% Zr, and 5% M. It is understood that the SiZr alloy target or SiZrM alloy target may also contain unavoidable impurity elements, such as Fe (iron), Cr (chromium), Ca (calcium), Ti (titanium), Cu (copper), Mn (manganese), O (oxygen), and N (nitrogen), etc., with the content of these impurity elements being less than 0.1%, more preferably less than 0.01%.
[0052] From the perspective of balancing the hardness and refractive index of the SiZrMOy layer, the M content in the SiZrM alloy target is preferably 0.1%-15%, specifically 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., more preferably 1%-14%, or 2%-12%, or 5%-10%. It is understood that when M is selected from two or more combinations of W, Nb, Ta, Y, Hf, and Al, the M content is the sum of the contents of the two or more combinations. For example, if the content of M is 10%, when M is only one element, it can be 10% Al, or 10% W, or 10% Nb; when M is a combination of two elements, it can be 8% Al and 2% W, or 5% Al and 5% Ta, or 4% Nb and 6% Y; when M is a combination of three elements, it can be 3% Al, 3% W and 4% Hf, or 2% Ta, 3% Y and 5% Al; when M is a combination of four elements, it can be 4% Al, 2% W, 2% Hf and 2% Nb.
[0053] Preferably, when M is selected from two or more combinations of W, Nb, Ta, Y, Hf, and Al, the mass ratio between the element with the highest content and the element with the lowest content in the combination is 1-2, specifically 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2; for example, if M is 5% Al and 7% Ta, then the mass ratio of Ta to Al is 1.2; another example is if M is 3% Al, 3% W, and 4% Hf, then the mass ratio of Hf to Al or W is 1.33; more preferably, the mass ratio is 1-1.5.
[0054] The target power source for the outermost protective layer 141 is preferably a high-power pulsed magnetron sputtering power source (HiPIMS power source). Using a HiPIMS power source, hundreds of kilowatts or even megawatts of instantaneous high power can be supplied to the sputtering target within a short pulse during the sputtering deposition process. This increases the ionization rate of the sputtering target, resulting in more chemical bonds in the SiZrOx and SiZrMOy layers, enhancing the adhesion of the outermost protective layer 141 and improving its surface hardness. Simultaneously, it allows for a more porous deposition of the SiZrOx and SiZrMOy layers, further reducing the refractive index of the outermost protective layer 141. Preferably, the operating voltage for magnetron sputtering of the outermost protective layer 141 is 550V-1200V, the operating current is 200A-1000A, and the duty cycle is 5%-15%. Examples of the operating voltage include 550V, 600V, 650V, 700V, 750V, 800V, 850V, 900V, 950V, 1000V, 1050V, 1100V, 1150V, and 1200V; more preferably, the operating voltage is 600V-1000V. Examples of the operating current include 200A, 300A, 400A, 500A, 600A, 700A, 800A, 900A, and 1000A; more preferably, the operating current is 500A-900A. Examples of the duty cycle include 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0055] The outer glass plate 11 is made of transparent or tinted glass, with a thickness of 0.7 mm to 4 mm and a visible light transmittance greater than 70%. The inner glass plate 13 is also made of transparent or tinted glass, with a thickness of 0.7 mm to 4 mm and a visible light transmittance greater than 70%. Preferably, at least one of the outer glass plate 11 and the inner glass plate 13 is tinted glass, thereby providing a better display background for the HUD image and improving the contrast between the HUD image and the display background. The total iron content (as Fe2O3) of the transparent glass is less than or equal to 0.1%, even less than or equal to 0.05%, and further less than or equal to 0.01%, and the visible light transmittance of the transparent glass is 80% to 95%. The total iron content (as Fe2O3) of the tinted glass is 0.1% to 0.8%, even more than 0.1% to 0.5%, and the visible light transmittance of the tinted glass is 75% to 90%. In this application, it is preferred that the thickness of the outer glass plate 11 is greater than the thickness of the inner glass plate 13. The thickness of the outer glass plate 11 can be 2.1 mm to 4 mm, and the thickness of the inner glass plate 13 can be 0.7 mm to 1.8 mm. For example, the thickness of the outer glass plate 11 is at least 0.3 mm greater than the thickness of the inner glass plate 13. Using a thinner inner glass plate 13 can form an asymmetrical thickness laminated glass structure. While reducing the total thickness of the head-up display glass 200 to achieve lightweighting, it can also improve the strength of the head-up display glass 200 to a certain extent and further improve the quality of the HUD image.
[0056] The thermoplastic interlayer 12 is a transparent or colored thermoplastic polymer film, and its visible light transmittance is greater than 70%. The visible light transmittance of the thermoplastic interlayer 12 can be, but is not limited to, 75%, 80%, 85%, or 90%. The thermoplastic interlayer 12 is used to bond the outer glass plate 11 and the inner glass plate 13 together to form a laminated glass structure. Preferably, the thermoplastic interlayer 12 is a colored thermoplastic polymer film. The colored thermoplastic polymer film can be gray, green, or blue, thereby providing a better display background for the HUD image and improving the contrast between the HUD image and the display background. The material of the thermoplastic polymer film can be selected from at least one of polyvinyl butyral (PVB), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), and ionic polymer (SGP). The thickness of the thermoplastic intermediate layer 12 is 0.38 mm to 2.28 mm, and can be, but is not limited to, 0.38 mm, 0.76 mm, 1.14 mm, 1.52 mm, 1.9 mm, 2.28 mm, or other values between 0.38 mm and 2.28 mm.
[0057] In this application, the thermoplastic interlayer 12 can be a single-layer structure or a multi-layer structure. Examples of multi-layer structures include double-layer, triple-layer, quadruple-layer, and five-layer structures. The thermoplastic interlayer 12 can also have other functions, such as providing at least one colored area as a shaded zone to reduce sunlight interference with the human eye, adding infrared absorbers to provide sun protection or heat insulation, adding ultraviolet absorbers to provide ultraviolet protection, or having at least one layer of the multi-layer structure with a higher plasticizer content to provide sound insulation. Traditional head-up display glass typically uses wedge-shaped PVB with a wedge angle of at least 0.3 mrad to eliminate ghosting (secondary images), making the design, production, and debugging of head-up display systems difficult. The head-up display glass 200 provided in this application can be directly replaced by a standard thermoplastic interlayer of equal thickness, where the wedge angle is essentially equal to 0. It is understood that this application may also use a wedge-shaped thermoplastic interlayer with a smaller wedge angle. Preferably, the wedge angle of the wedge-shaped thermoplastic interlayer is 0.01 to 0.15 mrad, specifically 0.01 mrad, 0.02 mrad, 0.03 mrad, 0.04 mrad, 0.05 mrad, 0.06 mrad, 0.07 mrad, 0.08 mrad, 0.09 mrad, 0.10 mrad, 0.11 mrad, 0.12 mrad, 0.13 mrad, 0.14 mrad, 0.15 mrad, etc. This can further eliminate the perspective ghosting caused by objects in the vehicle's external environment passing through the head-up display glass 200. The wedge-shaped thermoplastic interlayer with a smaller wedge angle can be obtained through a simple stretching process, thereby eliminating both reflection ghosting and perspective ghosting in a low-cost manner, and obtaining a higher quality head-up display image and viewing effect.
[0058] The head-up display glass 200 further includes a light-shielding layer 15, which is disposed around the perimeter of the head-up display glass 200. The area with the light-shielding layer 15 has low visible light transmittance, serving to shield and protect interior components, preventing them from aging and damage due to direct sunlight, thus extending their lifespan. Simultaneously, the light-shielding layer 15 also obscures interior components, ensuring an aesthetically pleasing appearance from the outside. The area of the head-up display glass 200 with the light-shielding layer 15 is the peripheral area, where the visible light transmittance is less than or equal to 5%, preferably less than or equal to 3%, more preferably less than or equal to 1%, or even essentially zero (opaque). The area of the head-up display glass 200 without the light-shielding layer 15 is the central area. The head-up display glass 200 provided in this application can be used as a windshield; to meet safety standards, the visible light transmittance of the central area is greater than or equal to 70%.
[0059] exist Figures 2 to 7 In the process, the transparent nanofilm 14 further includes at least one stacked structure disposed between the fourth surface 132 and the outermost protective layer 141. Each stacked structure includes a high refractive index layer and a low refractive index layer stacked sequentially. The refractive index of the high refractive index layer is 1.61-2.75, and the refractive index of the low refractive index layer is 1.35-1.60.
[0060] The material of the high refractive index layer is selected from at least one of the oxides or nitrides or oxynitrides of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, and Ta. Specific examples of materials for the high refractive index layer include zinc tin oxide (ZnSnOt), magnesium-doped zinc tin oxide (ZnSnMgOt), titanium-doped zinc tin oxide (ZnSnTiOt), zirconium-doped zinc tin oxide (ZnSnZrOt), silicon aluminum nitride (SiAlNt), silicon zirconium nitride (SiZrNt), silicon aluminum oxynitride (SiAlONt), silicon zirconium oxynitride (SiZrONt), silicon nitride (SiNt), zirconium oxide (ZrOt), zinc oxide (ZnOt), aluminum-doped zinc oxide (AZO), hafnium and aluminum-doped zinc oxide (HAZO), yttrium-doped zinc oxide (YZO), gallium-doped zinc oxide (GZO), titanium oxide (TiOt), niobium oxide (Nb2O5), and silicon zirconium nitride (SiZrNt). The high refractive index layer is formed by magnetron sputtering, and the value of t can be determined based on whether the magnetron sputtering process uses stoichiometry, substoichiometry, or superstoichiometry for deposition.
[0061] In some embodiments, for the purposes of facilitating production cost control and process convenience, the target power supply for the high refractive index layer is a medium-frequency magnetron sputtering power supply (MF power supply), and the duty cycle for magnetron sputtering the high refractive index layer is 100%.
[0062] In other embodiments, to better achieve the optical, mechanical, and color properties of the transparent nanofilm 14, the target power supply for at least one of the high-refractive-index layers is a high-power pulsed magnetron sputtering (HiPIMS) power supply, with a duty cycle of 5%-15% for magnetron sputtering at least one of the high-refractive-index layers. It is understood that the target power supply for one of the multiple high-refractive-index layers may be a HiPIMS power supply, while the remaining target power supplies may be MF power supplies; alternatively, all target power supplies for the high-refractive-index layers may be HiPIMS power supplies. From the perspective of balancing cost and performance, it is preferable that the target power supply for the high-refractive-index layer in the stacked structure closest to the outermost protective layer is a HiPIMS power supply.
[0063] The material of the low-refractive-index layer is selected from at least one of oxides, nitrides, carbides, or fluorides of Si, Al, and Mg. Specific examples of the material for the low-refractive-index layer include silicon oxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), and magnesium fluoride (MgF). The low-refractive-index layer is formed by magnetron sputtering, with the target power supply being a medium-frequency magnetron sputtering power supply, and the duty cycle for magnetron sputtering the low-refractive-index layer being 100%.
[0064] exist Figures 2 to 5 In this structure, the outermost protective layer 141 is in direct contact with the first low-refractive-index layer 143, the second low-refractive-index layer 145, and the third low-refractive-index layer 147 in the closest stacked structure. Together, the outermost protective layer 141, the first low-refractive-index layer 143, the second low-refractive-index layer 145, and the third low-refractive-index layer 147 constitute the outermost low-refractive-index layer of the transparent nanofilm 14. The outermost protective layer 141 serves both as the outermost layer of the transparent nanofilm 14 to improve its mechanical properties and, together with the first low-refractive-index layer 143, the second low-refractive-index layer 145, and the third low-refractive-index layer 147, adjusts the optical properties and appearance color of the transparent nanofilm 14, which is beneficial for enabling the transparent nanofilm 14 to be used exposed on the interior surface of vehicle glass. Simultaneously, it also helps to reduce production costs. Preferably, the physical thickness of the outermost protective layer 141 is 30nm-110nm. More preferably, the physical thickness of the outermost protective layer 141 is 30nm-100nm, or 30nm-90nm, or 30nm-80nm, or 30nm-70nm, or 30nm-60nm, etc.
[0065] like Figure 2 As shown, the transparent nanofilm 14 includes a stacked structure comprising a first high-refractive-index layer 142 and a first low-refractive-index layer 143. Specifically, the transparent nanofilm 14 comprises a first high-refractive-index layer 142, a first low-refractive-index layer 143, and an outermost protective layer 141 sequentially deposited on the fourth surface 132. The outermost protective layer 141 is in direct contact with the first low-refractive-index layer 143 in the stacked structure. The physical thickness of the first high-refractive-index layer 142 is 30 nm-120 nm, and the physical thickness of the first low-refractive-index layer 143 is 5 nm-90 nm. Optionally, the physical thickness of the first low-refractive-index layer 143 in the stacked structure is greater than the physical thickness of the outermost protective layer 141.
[0066] like Figure 3As shown, the transparent nanofilm 14 comprises two stacked structures. The first stacked structure includes a first high-refractive-index layer 142 and a first low-refractive-index layer 143, and the second stacked structure includes a second high-refractive-index layer 144 and a second low-refractive-index layer 145. Specifically, the transparent nanofilm 14 comprises a first high-refractive-index layer 142, a first low-refractive-index layer 143, a second high-refractive-index layer 144, a second low-refractive-index layer 145, and an outermost protective layer 141 sequentially deposited on the fourth surface 132. The outermost protective layer 141 is in direct contact with the second low-refractive-index layer 145 in the second stacked structure. The physical thickness of the first high-refractive-index layer 142 is 5 nm-190 nm, the physical thickness of the first low-refractive-index layer 143 is 5 nm-110 nm, the physical thickness of the second high-refractive-index layer 144 is 30 nm-120 nm, and the physical thickness of the second low-refractive-index layer 145 is 5 nm-90 nm. Optionally, the physical thickness of the second low-refractive-index layer 145 in the second stacked structure is greater than the physical thickness of the outermost protective layer 141.
[0067] like Figure 4 As shown, the transparent nanofilm 14 includes three stacked structures. The first stacked structure includes a first high refractive index layer 142 and a first low refractive index layer 143. The second stacked structure includes a second high refractive index layer 144 and a second low refractive index layer 145. The third stacked structure includes a third high refractive index layer 146 and a third low refractive index layer 147. Specifically, the transparent nanofilm 14 includes a first high refractive index layer 142, a first low refractive index layer 143, a second high refractive index layer 144, a second low refractive index layer 145, a third high refractive index layer 146, a third low refractive index layer 147, and an outermost protective layer 141, which are sequentially deposited on the fourth surface 132. The outermost protective layer 141 is in direct contact with the third low refractive index layer 147 in the third stacked structure. The physical thickness of the first high-refractive-index layer 142 is 120nm-190nm, the physical thickness of the first low-refractive-index layer 143 is 5-50nm, the physical thickness of the second high-refractive-index layer 144 is 110nm-190nm, the physical thickness of the second low-refractive-index layer 145 is 20nm-110nm, the physical thickness of the third high-refractive-index layer 146 is 30nm-120nm, and the physical thickness of the third low-refractive-index layer 147 is 5nm-90nm. Optionally, the physical thickness of the third low-refractive-index layer 147 in the third stacked structure is greater than the physical thickness of the outermost protective layer 141.
[0068] In some embodiments, at least one high-refractive-index layer is composed of multiple high-refractive-index sublayers, that is, at least one high-refractive-index layer includes at least two high-refractive-index sublayers, and the refractive indices of two adjacent high-refractive-index sublayers are different. To better achieve the comprehensive requirements of vehicle window glass in terms of optical performance, mechanical properties, and appearance color of the transparent nanofilm 14, it is preferable that the refractive index of the high-refractive-index sublayer closest to the fourth surface 132 is 1.61-2.30, and the refractive index of the high-refractive-index sublayer furthest from the fourth surface is 2.10-2.75. Preferably, the refractive index of the high-refractive-index sublayer furthest from the fourth surface is at least 0.3 greater than the refractive index of the high-refractive-index sublayer closest to the fourth surface 132. Considering the advantages of production cost control and the convenience of film system design, it is preferable that the at least one high-refractive-index layer includes two or three high-refractive-index sublayers.
[0069] like Figure 5 As shown, the transparent nanofilm 14 includes two stacked structures. The first stacked structure includes a first high refractive index layer 142 and a first low refractive index layer 143. The second stacked structure includes a second high refractive index layer 144 and a second low refractive index layer 145. The second high refractive index layer 144 includes two high refractive index sublayers, namely a high refractive index sublayer 1441 that is in direct contact with the first low refractive index layer 143 and a high refractive index sublayer 1442 that is in direct contact with the second low refractive index layer 145. The refractive index of the high refractive index sublayer 1441 can be exemplified as 1.9-2.2, and the refractive index of the high refractive index sublayer 1442 can be exemplified as 2.5-2.75.
[0070] exist Figure 6 and Figure 7 In this structure, an optical adjustment layer 150 is disposed between the outermost protective layer 141 and the nearest low-refractive-index layer in the stacked structure. The refractive index of the optical adjustment layer 150 is 2.10-2.75. The outermost protective layer 141 independently constitutes the outermost low-refractive-index layer of the transparent nanofilm 14, which is more conducive to improving the hardness, wear resistance, and scratch resistance of the transparent nanofilm 14. At the same time, together with the optical adjustment layer 150, it forms a new stacked structure, which enables the transparent nanofilm 14 to maintain a high reflectivity for P-polarized light to ensure high brightness and high contrast of the HUD image, and is also more conducive to the exposed use of the transparent nanofilm 14 on the interior surface of the vehicle. Preferably, the physical thickness of the outermost protective layer 141 is 60nm-120nm. More preferably, the physical thickness of the outermost protective layer 141 is 70nm-120nm, or 80nm-120nm, or 90nm-120nm, or 100nm-120nm.
[0071] The optical adjustment layer 150 is made of at least one of oxides or nitrides or oxynitrides of Zr, Nb, Si, Sb, Sn, Zn, In, Al, Ni, Cr, Mg, Mn, V, W, Hf, Ta, Mo, Ga, Y, Bi, and Ta. Specific examples of the material for the optical adjustment layer 150 include zinc tin oxide (ZnSnOt), silicon nitride (SiNt), zirconium oxide (ZrOt), titanium oxide (TiOt), niobium oxide (Nb2O5), and silicon zirconium nitride (SiZrNt). The optical adjustment layer 150 is formed by magnetron sputtering. The target power supply for the optical adjustment layer 150 is a medium-frequency magnetron sputtering power supply (MF power supply) or a high-power pulsed magnetron sputtering power supply (HiPIMS power supply). When using an MF power supply, the duty cycle of magnetron sputtering of the optical adjustment layer 150 is 100%. When using a HiPIMS power supply, the duty cycle of magnetron sputtering of the optical adjustment layer 150 is 5%-15%. The value of t can be determined based on whether the magnetron sputtering process uses stoichiometry, substoichiometry, or superstoichiometry for deposition.
[0072] like Figure 6 As shown, the transparent nanofilm 14 includes a stacked structure and an optical adjustment layer 150. The stacked structure includes a first high-refractive-index layer 142 and a first low-refractive-index layer 143. Specifically, the transparent nanofilm 14 comprises the first high-refractive-index layer 142, the first low-refractive-index layer 143, the optical adjustment layer 150, and an outermost protective layer 141 sequentially deposited on the fourth surface 132. The optical adjustment layer 150 is in direct contact with the first low-refractive-index layer 143. The outermost protective layer 141 and the optical adjustment layer 150 together form a new stacked structure. The transparent nanofilm 14 effectively comprises two stacked structures. The physical thickness of the optical adjustment layer 150 is 30nm-120nm. Optionally, the physical thickness of the outermost protective layer 141 is greater than the thickness of the optical adjustment layer 150.
[0073] like Figure 7 As shown, the optical adjustment layer 150 is composed of multiple optical adjustment sub-layers, that is, the optical adjustment layer 150 includes at least two optical adjustment sub-layers, namely a first optical adjustment sub-layer 1501 that is in direct contact with the first low refractive index layer 143 and a second optical adjustment sub-layer 1502 that is in direct contact with the outermost protective layer 141. The refractive index of the first optical adjustment sub-layer 1501 can be, for example, 1.9-2.2, and the refractive index of the second optical adjustment sub-layer 1502 can be, for example, 2.5-2.75.
[0074] The head-up display glass 200 provided in this application maintains a high reflectivity for P-polarized light to ensure high brightness and high contrast of the HUD image. Preferably, the reflectivity of the head-up display glass for P-polarized light with wavelengths of 629nm, 529nm, and 469nm incident at a 65° incident angle is R1, R2, and R3, respectively, where R1 ≥ 19%, R2 ≥ 19%, and R3 ≥ 19%. As the reflectivity of the head-up display glass 200 for P-polarized light increases, the emission power of the projection device 100 can be reduced, the heat generated by the projection device 100 can be reduced, and even the size of the projection device 100 can be reduced. Simultaneously, the head-up display glass 200 provided in this application unexpectedly makes the reflection spectrum of P-polarized light smoother, which is beneficial for achieving neutral color display of the HUD image. Preferably, the difference between the maximum and minimum values of R1, R2, and R3 is less than or equal to 3%, more preferably less than or equal to 2%, and even more preferably less than or equal to 1%.
[0075] Comparative Examples 1-3 and Examples 1-10
[0076] This application prepares a 2.1 mm thick transparent glass substrate, and deposits the film structures of Comparative Examples 1-3 and Examples 1-10 on the surface of the transparent glass substrate by magnetron sputtering. The transparent glass substrate with the film structure is subjected to high-temperature heat treatment at at least 500°C. Then, the refractive index n and extinction coefficient k of the test samples of Comparative Examples 1-3 and Examples 1-10 are measured, and the measurement results are recorded in Table 1.
[0077] Comparative Example 1: Transparent glass substrate / SiO2 layer, sputtering target is pure Si target.
[0078] Comparative Example 2: Transparent glass substrate / SiZrO X The sputtering target is a SiZr alloy target, which contains 64% Si and 36% Zr.
[0079] Comparative Example 3: Transparent glass substrate / ZrO2 layer, sputtering target is ZrO 1.4 Ceramic target.
[0080] In the magnetron sputtering process of Comparative Examples 1-3, the process gases were Ar and O2, the target power supply was MF power supply, and the duty cycle was 100%.
[0081] Examples 1-3: Transparent glass substrate / SiZrO X The sputtering target is a SiZr alloy target, which contains 64% Si and 36% Zr.
[0082] Example 4: Transparent glass substrate / SiZrAlO XThe sputtering target is a SiZrAl alloy target, which contains 58.5% Si, 36.5% Zr and 5% Al.
[0083] Examples 5-6: Transparent glass substrate / SiZrAlWO3 X The sputtering target is a SiZrAlW alloy target, which contains 55% Si, 35% Zr, 5% Al and 5% W.
[0084] Example 7: Transparent glass substrate / SiZrAlTaO X The sputtering target is a SiZrAlTa alloy target, which contains 54% Si, 34% Zr, 5% Al and 7% Ta.
[0085] Examples 8-9: Transparent glass substrate / SiZrYNbO X The sputtering target is a SiZrYNb alloy target, which contains 56% Si, 34% Zr, 5% Y and 5% Nb.
[0086] Example 10: Transparent glass substrate / SiZrAlTaO X The sputtering target is a SiZrAlTa alloy target, which contains 71% Si, 17% Zr, 5% Al and 7% Ta.
[0087] In the magnetron sputtering process of Examples 1-10, the process gases are Ar and O2, the target power supply is a HiPIMS power supply, and the duty cycle is 5% to 15%.
[0088] Table 1: Measurement results of test samples from Comparative Examples 1-3 and Examples 1-10
[0089]
[0090]
[0091] As can be seen from Table 1, in Comparative Examples 1 and 2, magnetron sputtering with an MF power supply can obtain SiO2 layers with a refractive index n ≤ 1.6 and SiZrO2 layers. XThe extinction coefficient k of the two layers is 0. Comparative Example 3 uses an MF power supply for magnetron sputtering to obtain a high refractive index ZrO2 layer with a refractive index n = 2.24 and an extinction coefficient k = 0.00054. Compared with Comparative Examples 1-3, Examples 1-10 use a HiPIMS power supply for magnetron sputtering to obtain SiZrOx or SiZrMOy layers with a refractive index n = 1.50-1.60 using a SiZr alloy target or a SiZrM alloy target. While maintaining a low refractive index, the extinction coefficient k of the SiZrOx or SiZrMOy layers is increased to 0.00001-0.001, making the SiZrOx or SiZrMOy layers more suitable as the outermost protective layer 141 of the transparent nanofilm 14. This makes the reflection spectrum of the transparent nanofilm 14 for P-polarized light smoother, which is beneficial for achieving neutral color display of HUD images. Optionally, the refractive index n of the SiZrOx layer or SiZrMOy layer as the outermost protective layer 141 is 1.50-1.57, or 1.51-1.56, or 1.52-1.55, etc. Optionally, the extinction coefficient k of the SiZrOx layer or SiZrMOy layer as the outermost protective layer 141 is 0.00003-0.0009, or 0.00008-0.0008, or 0.0001-0.0007.
[0092] Comparative Examples 4-5 and Examples 11-12
[0093] Prepare an outer glass plate 11, a thermoplastic interlayer 12, and an inner glass plate 13. The outer glass plate 11 is a 2.1 mm thick transparent glass (clear glass), the thermoplastic interlayer 12 is a 0.76 mm thick standard transparent PVB, and the inner glass plate 13 is a 2.1 mm thick transparent glass (clear glass). The transparent nanofilms in Comparative Examples 4-5 and Examples 11-12 are deposited on the fourth surface 132 of the inner glass plate 13 by magnetron sputtering. Then, the glass is processed and manufactured according to the vehicle glass manufacturing process to obtain the head-up display glass in Comparative Examples 4-5 and Examples 11-12.
[0094] The projection device was combined with the head-up display glass of Comparative Examples 4-5 and Examples 11-12 to form a head-up display system. The projection device generated projection light containing at least 99% P-polarized light. The projection light was incident on the transparent nanofilm at an incident angle of 38°-85°. The position of the projection device and the incident angle of the projection light were adjusted to make the head-up display image visible to the observer as clear as possible. The P-polarized light reflectance, reflected color, visible light transmittance and film hardness were measured and calculated, and the test results were recorded in Table 2.
[0095] P-polarized light reflectivity: The reflectivity of the head-up display glass to P-polarized light with wavelengths of 629nm, 529nm, and 469nm incident at an incident angle of 65° is calculated from the transparent nanofilm side according to ISO9050, and is R1, R2, and R3, respectively.
[0096] Reflected color: Measured from the first surface side at a 0° incident angle, based on a D65 light source and a 10° field of view, the a and b values are calculated according to the CIE Lab color model. The a value represents the red-green value, and the b value represents the yellow-blue value.
[0097] Visible light transmittance TL: The transmittance of visible light with wavelengths of 380nm-780nm through the head-up display glass, measured and calculated according to ISO9050.
[0098] Film hardness test: Pencil hardness test was performed on the transparent nanofilm according to GB / T 6739-2006; Neutral pen hardness test was performed using a 0.5mm ballpoint pen lead instead of a pencil according to GB / T 6739-2006; Abrasion resistance test was performed on the transparent nanofilm according to GB / T 18915.2-2013.
[0099] Table 2: Test results of Comparative Examples 4-5 and Examples 11-12
[0100]
[0101] In Table 2: the TiOt sublayer of the second high refractive index layer and the outermost protective layer were both magnetron sputtered using a HiPIMS power supply, while the other film layers were magnetron sputtered using an MF power supply.
[0102] Neither the transparent nanofilms in Comparative Examples 4 nor 5 contained an outermost protective layer. The layer furthest from the fourth surface in the transparent nanofilm of Comparative Example 4 was the SiO2 layer of Comparative Example 1, while the layer furthest from the fourth surface in the transparent nanofilm of Comparative Example 5 was the SiZrOx layer of Comparative Example 2. The visible light transmittance, P-polarized light reflectance, and reflected color of the head-up display glass in Comparative Examples 4 and 5 all met the requirements for realizing the head-up display function. However, the film hardness of the transparent nanofilms in Comparative Examples 4 and 5 was not conducive to their exposed use on vehicle interior surfaces. Furthermore, compared to Comparative Example 4, the refractive index of the SiZrOx layer in Comparative Example 5 was greater than that of the SiO2 layer in Comparative Example 4, resulting in a certain degree of decrease in the P-polarized light reflectance of Comparative Example 5.
[0103] Example 11 uses the SiZrOx layer from Example 1 as the outermost protective layer, and Example 12 uses the SiZrAlTaO layer from Example 7. XThe outermost protective layer, together with the second low-refractive-index layer, constitutes the outermost low-refractive-index layer of the transparent nanofilm. The visible light transmittance, P-polarized light reflectance, and reflected color of the head-up display glass in Examples 11 and 12 all meet the requirements for realizing the head-up display function. Furthermore, the film hardness of the transparent nanofilms in Examples 11 and 12 is beneficial for exposed use on vehicle interior surfaces. Specifically, the difference between the maximum and minimum values of the P-polarized light reflectance R1, R2, and R3 in Example 11 is less than or equal to 0.5%, and the difference between the maximum and minimum values of the P-polarized light reflectance R1, R2, and R3 in Example 12 is less than or equal to 3%.
[0104] Meanwhile, the SiZrOx layer in Example 11 and the SiZrAlTaO layer in Example 12 X The physical thickness of each layer is smaller than that of its second low-refractive-index layer, which also helps to reduce production costs.
[0105] Compared with Comparative Example 5, the refractive index of the SiZrOx layer in Example 11 is lower than that of the SiZrOx layer in Comparative Example 5, the extinction coefficient of the SiZrOx layer in Example 11 is greater than that of the SiZrOx layer in Comparative Example 5, and the reflectivity of P-polarized light in Example 11 is improved to a certain extent.
[0106] Examples 13-14
[0107] Prepare an outer glass plate 11, a thermoplastic interlayer 12, and an inner glass plate 13. The outer glass plate 11 is a 2.1 mm thick transparent glass (clear glass), the thermoplastic interlayer 12 is a 0.76 mm thick standard transparent PVB, and the inner glass plate 13 is a 2.1 mm thick transparent glass (clear glass). The transparent nanofilms in Examples 13-14 are deposited on the fourth surface 132 of the inner glass plate 13 by magnetron sputtering. Then, the glass is processed and manufactured according to the vehicle glass manufacturing process to obtain the head-up display glass in Examples 13-14.
[0108] The projection device and the head-up display glass of Examples 13-14 are combined to form a head-up display system. The projection device generates projection light containing at least 99% P-polarized light. The projection light is incident on the transparent nanofilm at an incident angle of 38°-85°. The position of the projection device and the incident angle of the projection light are adjusted so that the head-up display image that the observer can observe is as clear as possible. The P-polarized light reflectance, reflected color, visible light transmittance and film hardness are measured and calculated, and the test results are recorded in Table 3.
[0109] Table 3: Test Results of Examples 13-14
[0110]
[0111]
[0112] In Table 3: the outermost protective layer and the TiOt sublayer of the first high refractive index layer in Example 13 and the third high refractive index layer in Example 14 were all magnetron sputtered using a HiPIMS power supply, while the other film layers were magnetron sputtered using an MF power supply.
[0113] Example 13 uses the SiZrAlWOx layer from Example 5 as the outermost protective layer, and this outermost protective layer, together with the first low-refractive-index layer, constitutes the outermost low-refractive-index layer of the transparent nanofilm. Example 14 uses the SiZrYNbOx layer from Example 8 as the outermost protective layer, and this outermost protective layer, together with the third low-refractive-index layer, constitutes the outermost low-refractive-index layer of the transparent nanofilm. The visible light transmittance, P-polarized light reflectance, and reflected color of the head-up display glass in Examples 13 and 14 all meet the requirements for realizing the head-up display function. Furthermore, the film hardness of the transparent nanofilms in Examples 13 and 14 is beneficial for exposed use on vehicle interior surfaces. Specifically, the difference between the maximum and minimum values of the P-polarized light reflectance R1, R2, and R3 in Example 13 is less than or equal to 3%, and the difference between the maximum and minimum values of the P-polarized light reflectance R1, R2, and R3 in Example 14 is less than or equal to 1%.
[0114] Meanwhile, the physical thickness of the outermost protective layer in Examples 13 and 14 is smaller than the physical thickness of its nearest low-refractive-index layer, which also helps to reduce production costs.
[0115] Examples 15-18
[0116] Prepare an outer glass plate 11, a thermoplastic interlayer 12, and an inner glass plate 13. The outer glass plate 11 is a 2.1 mm thick transparent glass (clear glass), the thermoplastic interlayer 12 is a 0.76 mm thick standard transparent PVB, and the inner glass plate 13 is a 2.1 mm thick transparent glass (clear glass). The transparent nanofilms in Examples 15-18 are deposited on the fourth surface 132 of the inner glass plate 13 by magnetron sputtering. Then, the glass is processed and manufactured according to the vehicle glass manufacturing process to obtain the head-up display glass in Examples 15-18.
[0117] The projection device and the head-up display glass of Examples 15-18 are combined to form a head-up display system. The projection device generates projection light containing at least 99% P-polarized light. The projection light is incident on the transparent nanofilm at an incident angle of 38°-85°. The position of the projection device and the incident angle of the projection light are adjusted so that the head-up display image that the observer can observe is as clear as possible. The P-polarized light reflectivity, reflected color, visible light transmittance and film hardness are measured and calculated, and the test results are recorded in Table 4.
[0118] Table 4: Test Results of Examples 15-18
[0119]
[0120] In Table 4: the TiOt sublayer and the outermost protective layer in the optical conditioning layer were both magnetron sputtered using a HiPIMS power supply, while the other film layers were magnetron sputtered using an MF power supply.
[0121] Example 15 uses SiZrOx (n = 1.54, k = 0.00003) from Example 2 as the outermost protective layer. Example 16 uses SiZrOx (n = 1.50, k = 0.00008) from Example 3 as the outermost protective layer. Example 16 also uses SiZrAlOx (n = 1.54, k = 0.00005) from Example 4 as the outermost protective layer. Example 18 uses SiZrYNbOx (n = 1.56, k = 0.00064) from Example 9 as the outermost protective layer. The outermost protective layer of Examples 15-18 independently constitutes the outermost low-refractive-index layer of the transparent nanofilm. An optical adjustment layer is also provided between the outermost protective layer and the nearest low-refractive-index layer. Together, the outermost protective layer and the optical adjustment layer form a new stacked structure. The visible light transmittance, P-polarized light reflectance, and reflected color of the head-up display glass of Examples 15-18 all meet the requirements for realizing the head-up display function. The film hardness of the transparent nanofilm of Examples 15-18 is beneficial for exposed use on vehicle interior surfaces. Specifically, in Example 15, the difference between the maximum and minimum values of the P-polarized light reflectance R1, R2, and R3 is less than or equal to 0.5%; in Example 16, the difference is less than or equal to 1.5%; and in Examples 17-18, the difference is less than or equal to 1%.
Claims
1. A head-up display glass, characterized in that, The head-up display glass includes: Laminated glass, comprising an outer glass sheet, an inner glass sheet, and a thermoplastic interlayer disposed between the outer and inner glass sheets, wherein the outer glass sheet includes a first and a second surface facing away from each other, the inner glass sheet includes a third and a fourth surface facing away from each other, and the thermoplastic interlayer is disposed between the second and third surfaces; and A transparent nanofilm is disposed on the fourth surface. The transparent nanofilm is capable of reflecting P-polarized light. The transparent nanofilm includes an outermost protective layer that is furthest from the fourth surface. The outermost protective layer is a SiZrOx layer or a SiZrMOy layer, wherein x satisfies 1 < x < 3, y satisfies 1 < y < 3, and M is selected from one or more combinations of W, Nb, Ta, Y, Hf, and Al. The refractive index n of the SiZrOx layer or SiZrMOy layer, which serves as the outermost protective layer, is 1.50-1.60, and the extinction coefficient k of the SiZrOx layer or SiZrMOy layer, which serves as the outermost protective layer, is 0.00001-0.
001. The reflectivity of the head-up display glass to P-polarized light with wavelengths of 629nm, 529nm, and 469nm incident at an incident angle of 65° is R1, R2, and R3, respectively, wherein R1 ≥ 19%, R2 ≥ 19%, and R3 ≥ 19%.
2. The head-up display glass according to claim 1, characterized in that, The outermost protective layer has a pencil hardness ≥9H.
3. The head-up display glass according to claim 1, characterized in that, The physical thickness of the outermost protective layer is 30nm-120nm.
4. The head-up display glass according to claim 1, characterized in that, The outermost protective layer is formed by magnetron sputtering, and the sputtering target of the outermost protective layer is a SiZr alloy target or a SiZrM alloy target.
5. The head-up display glass according to claim 4, characterized in that, The SiZr alloy target comprises 50%-70% Si and 30%-50% Zr by mass percentage, and the SiZrM alloy target comprises 50%-75% Si, 10%-40% Zr and 0.1%-15% M.
6. The head-up display glass according to claim 5, characterized in that, M is selected from two or more combinations of W, Nb, Ta, Y, Hf, and Al, and the mass ratio between the most abundant element and the least abundant element in the combination is 1-2.
7. The head-up display glass according to claim 4, characterized in that, The target power supply for the outermost protective layer is a high-power pulsed magnetron sputtering power supply. The working voltage for magnetron sputtering of the outermost protective layer is 550V-1200V, the working current is 200A-1000A, and the duty cycle is 5%-15%.
8. The head-up display glass according to claim 1, characterized in that, The transparent nanofilm further includes at least one stacked structure disposed between the fourth surface and the outermost protective layer. Each stacked structure includes a high refractive index layer and a low refractive index layer stacked sequentially. The refractive index of the high refractive index layer is 1.61-2.75, and the refractive index of the low refractive index layer is 1.35-1.
60.
9. The head-up display glass according to claim 8, characterized in that, The high refractive index layer and the low refractive index layer are formed by magnetron sputtering. The target power supply for the low refractive index layer is a medium-frequency magnetron sputtering power supply, and the duty cycle for magnetron sputtering the low refractive index layer is 100%.
10. The head-up display glass according to claim 9, characterized in that, The target power supply for the high refractive index layer is a medium-frequency magnetron sputtering power supply, and the duty cycle for magnetron sputtering the high refractive index layer is 100%.
11. The head-up display glass according to claim 9, characterized in that, The target power supply for at least one of the high refractive index layers is a high-power pulsed magnetron sputtering power supply, and the duty cycle for magnetron sputtering at least one of the high refractive index layers is 5%-15%.
12. The head-up display glass according to claim 8, characterized in that, The outermost protective layer is in direct contact with the low-refractive-index layer in the closest stacked structure, and the physical thickness of the outermost protective layer is 30nm-110nm.
13. The head-up display glass according to claim 12, characterized in that, The physical thickness of the low-refractive-index layer in the closest stacked structure is greater than the physical thickness of the outermost protective layer.
14. The head-up display glass according to claim 8, characterized in that, An optical adjustment layer is also provided between the outermost protective layer and the low refractive index layer in the closest stacked structure. The refractive index of the optical adjustment layer is 2.10-2.75, and the physical thickness of the outermost protective layer is 60nm-120nm.
15. The head-up display glass according to claim 14, characterized in that, The physical thickness of the outermost protective layer is greater than the thickness of the optical adjustment layer.
16. The head-up display glass according to claim 14, characterized in that, The optical adjustment layer is formed by magnetron sputtering. The target power supply for the optical adjustment layer is a high-power pulsed magnetron sputtering power supply, and the duty cycle of magnetron sputtering of the optical adjustment layer is 5%-15%.
17. The head-up display glass according to claim 8, characterized in that, At least one high refractive index layer comprises at least two high refractive index sublayers, wherein the high refractive index sublayer closest to the fourth surface has a refractive index of 1.61-2.10 and the high refractive index sublayer furthest from the fourth surface has a refractive index of 2.11-2.
75.
18. The head-up display glass according to claim 1, characterized in that, 20.4%≤R1≤26.1%, 22.0%≤R2≤25.4%, 20.5%≤R3≤25.6%.
19. The head-up display glass according to claim 1, characterized in that, The difference between the maximum and minimum values of R1, R2, and R3 is less than or equal to 3%.
20. The head-up display glass according to claim 1, characterized in that: The difference between the maximum and minimum values of R1, R2, and R3 is less than or equal to 2%.
21. The head-up display glass according to claim 1, characterized in that: The difference between the maximum and minimum values of R1, R2, and R3 is less than or equal to 1%.
22. The head-up display glass according to claim 1, characterized in that: The refractive index n of the SiZrOx layer or SiZrMOy layer is 1.50-1.
57.
23. The head-up display glass according to claim 1, characterized in that: The refractive index n of the SiZrOx layer or SiZrMOy layer is 1.51-1.
56.
24. The head-up display glass according to claim 1, characterized in that: The refractive index n of the SiZrOx layer or SiZrMOy layer is 1.52-1.
55.
25. The head-up display glass according to claim 1, characterized in that: The extinction coefficient k of the SiZrOx or SiZrMOy layer, which serves as the outermost protective layer, is 0.00003-0.0009.
26. The head-up display glass according to claim 1, characterized in that: The extinction coefficient k of the SiZrOx or SiZrMOy layer, which serves as the outermost protective layer, is 0.00008-0.0008.
27. The head-up display glass according to claim 1, characterized in that: The extinction coefficient k of the SiZrOx or SiZrMOy layer, which serves as the outermost protective layer, is 0.0001-0.0007.
28. A head-up display system, characterized in that, The head-up display system includes a projection device and a head-up display glass as described in any one of claims 1-27. The projection device is used to generate projection light containing P-polarized light, wherein the proportion of P-polarized light in the projection light is greater than or equal to 80%, and the projection light is incident on the transparent nanofilm at an incident angle of 38° to 85°.
Citation Information
Patent Citations
Composite pane for head-up display systems with p-polarized radiation
CN116568501A
Coated glass, preparation method thereof and automobile glass assembly
CN114538791A
Head up display system
WO2022253659A1